Pengaruh Tekanan Publik terhadap Pengungkapan Laporan Tanggung Jawab Sosial Perusahaan - Achmad Wicaksono (Prodi Akuntansi UIN Sunan Ampel Surabaya, 2019)
This study aims to examine the effect of public pressure on disclosure of corporate social responsibility reports. This study uses a quantitative approach. This study uses secondary data which is an annual report of manufacturing companies listed on the Indonesia Stock Exchange in 2017. This study uses a purposive sampling method to obtain a sample of 111 manufacturing companies. This study uses multiple linear regression techniques for testing hypotheses using the SPSS program. The results of this study indicate that public pressure as measured by industry type has a significant influence on the Disclosure of Social Responsibility Reports of manufacturing companies listed on the Indonesia Stock Exchange in 2017 which can be shown from the significance value of Industry Type = 0,000 and simultaneous significance value = 0,000. From the results of the research Adjusted R² of 36.3% variation in disclosure of social responsibility that can be explained by the variables used in this study. While the rest is explained by other variables not used in the study.